2019
DOI: 10.13075/ijomeh.1896.01309
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the use of the McKenzie and Vojta methods to treat discopathy-associated syndromes in the pediatric population

Abstract: Objectives: This paper evaluates the efficacy of using the McKenzie and Vojta methods for patients with low back pain and the use of the DIERS Formetric 4D system as an objective diagnostic tool. Material and Methods: The study enrolled 28 patients aged 15-17 years old. The patients were hospitalized at the Department of Orthopedics and Traumatology of the Świętokrzyskie Center for Pediatrics in Kielce with a diagnosis of back pain associated with a discopathy. The patients were rehabilitated according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…5 Too excessive thoracic kyphosis and too shallow lumbar lordosis correlate with the occurrence of discopathy, which is a serious clinical problem in older children. 6 This position is also accompanied by hyperextension of the head and shoulders retraction ( Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…5 Too excessive thoracic kyphosis and too shallow lumbar lordosis correlate with the occurrence of discopathy, which is a serious clinical problem in older children. 6 This position is also accompanied by hyperextension of the head and shoulders retraction ( Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…Our subjects demonstrated similar findings when performing an active retraction exercise and increased the foramen area from C2/3 to C6/7 by 6.63–13.51%. This scenario may verify the efficacy of the retraction exercise for relieving the nerve compression within an intervertebral foramen [ 15 , 16 ]. Although there is not much dynamic imaging evidence indicating this phenomenon, these previous findings and our results coincidentally suggest that therapeutic intervention methods may normalize the posture to physiological reference ranges and may thus be effective in the treatment of patients with neck or back pain.…”
Section: Discussionmentioning
confidence: 98%
“…Active spinal exercise is a nonsurgical interventional procedure used for treatment of chronic neck and back disorders. The spinal approach postulated by McKenzie indicated that compensatory pressure on the disc in the direction of the lesion can reduce the displacement of the nucleus in the disc [ 16 , 18 , 19 ]. The 8-week spinal therapeutic exercises in the present study mainly included end-range repeated cervical retraction, extension, and lateral flexion movements to the lesion in order to reduce the nucleus displacement and peripheralization inside the disc (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, we decided 15 min of reflex locomotion stimulation time to ensure that a sufficient amount of data was collected for the statistical analysis. However, the duration of stimulation varies across different studies [11][12][13][14][15][16][17][18][47][48][49][50]. Another study [13] with a similar design showed changes in cingulate cortex, premotor, and supplementary cortical areas during an 8 min-long reflex locomotion stimulation.…”
Section: Discussionmentioning
confidence: 99%